2018
DOI: 10.5846/stxb201704280784
|View full text |Cite
|
Sign up to set email alerts
|

Ecological risk assessment of an ecological migrant resettlement region based on landscape structure: A case study of Hongsibu in Ningxia

Abstract: Wang P,Wang Y J,Liu X P,Chen X,Kong F X.Ecological risk assessment of an ecological migrant resettlement region based on landscape structure: A case study of Hongsibu in Ningxia.Acta Ecologica Sinica,2018,38(8) : • .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Numerous studies had similar results. For example, Liu [67] and Wang [68] found that the landscape pattern of construction land was riskier than other types in different landscape types. By 2030, the demand for population and construction land in the study area will inevitably increase.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies had similar results. For example, Liu [67] and Wang [68] found that the landscape pattern of construction land was riskier than other types in different landscape types. By 2030, the demand for population and construction land in the study area will inevitably increase.…”
Section: Discussionmentioning
confidence: 99%
“…This risk unit segmentation method can be used to effectively analyze ecological risk patterns and accurately control risk management zoning. For research purposes, the related research on ecological risk paid more attention to the spatial and temporal differences in ecological risk [24,47], risk accumulation effects [21] and risk prediction [25,46]. Specific suggestion for ecological restoration based on differentiated risk management categories is relatively rare and thus, it is often difficult for risk assessment results to inform more specific applications.…”
Section: Discussionmentioning
confidence: 99%
“…where LLI k denotes the landscape loss index of a small watershed k; n is the number of landscape types; E i is the landscape disturbance index of landscape i; F i is the landscape vulnerability index of landscape i; S ki is the area of landscape components i in a small watershed k; and S k is the total area of a small watershed k. By referring to previous studies [21,24,46,47], the detailed calculation methods of E i and F i were given in Table 3. Table 3.…”
Section: Impairmentmentioning
confidence: 99%
See 2 more Smart Citations